EFFICIENCY LEVEL OF ADMINISTRATIVE PERFORMANCE OF MANAGERS OF ATHLETIC TALENT IN TERMS OF WORKING EMPLOYEES - hasan, solaf; Sami Yousif , Faris (Journal of Physical Education, 2023)
The aim of the research is to build a measure of the efficiency of the level of administrative performance of the managers of sports talent in terms of the working employees, and to identify the level of their efficiency from the point of view of the employees working in these centers. It is the extent of the efficiency of the level of administrative performance of the managers of athletic talent in succeeding in their management of the centers for the care of sports talent, and the research community was identified from the employees working in the centers for the care of sports talent, which numbered (329) employees, and the research sample was chosen from the research community itself, and the researchers conducted the process of statistical analysis of phrases The scale to ensure the availability of the scientific conditions for the scale represented by honesty and reliability, and the scale consists of ( 33) phrase, applied to the research sample, and the two researchers concluded that the directors of talent nurturing centers enjoy a level of performance is below average, and it needs development programs that contribute to evaluating the work of managers, and that the strategic plans developed by the Ministry for these centers must take into account the development programs for managers and employees.